Closing performance of the Thomson-coil actuator for a 110 kV FMS - Yannan Zhou; Yulong Huang; Weijie Wen; Keke Sun; Bo Men; Jibin Zhu (The Journal of Engineering, 2019)
In the 500 kV hybrid high-voltage direct current (HVDC) circuit breaker, there are five 110 kV fast mechanical switches (FMSs) in the nominal current path. When the detection system detects the failure of the hybrid circuit breaker, in order to protect the disconnectors or semiconductors, the FMSs are required to close quickly. The closing drive technology can be divided into two categories, based on the closing speed of the Thomson-coil actuator. One is based on the conventional closing drive, the open−close operating time of which is 20.0 ms. The other type is based on the fast closing drive, which is used under fault conditions and the total time is ∼7.5 ms. A 110 kV/3 kA prototype FMS employing an interrupter with a 30 mm maximum open gap and 4 kg total moving mass has been modelled based on the equivalent circuit method. Through the simulation, the effect of discharging time sequence on open−close operation has been studied, and the general timing control design principle has been provided.